2005
DOI: 10.1093/pcp/pci030
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Class-1 Non-symbiotic Hemoglobin Genes by Nitrate, Nitrite and Nitric Oxide in Cultured Rice Cells

Abstract: Non-symbiotic hemoglobins (ns-Hbs) are found in all plants, although their physiological function remains to be determined. The present study was undertaken to explore the mode of induction of ns-Hb genes by metabolites of nitrate assimilation using cultured rice (Oryza sativa L.) cells. Two class-1 ns-Hb genes, ORYsa GLB1a and ORYsa GLB1b, were strongly induced by nitrate, nitrite and nitric oxide (NO) donors, S-nitroso-N-acetylpenicillamine and sodium nitroprusside. The rapid and transient accumulation of OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 44 publications
2
57
0
Order By: Relevance
“…Hb induction is observed in response to nitrate (Nie and Hill, 1997), nitrite and NO treatment (Ohwaki et al, 2005). It is known that in hypoxic conditions, nitrate reductase is usually induced and nitrite is accumulated (Morard et al, 2004).…”
Section: I T O C Ho N D R I a U N D E R H Y P O X I Amentioning
confidence: 99%
“…Hb induction is observed in response to nitrate (Nie and Hill, 1997), nitrite and NO treatment (Ohwaki et al, 2005). It is known that in hypoxic conditions, nitrate reductase is usually induced and nitrite is accumulated (Morard et al, 2004).…”
Section: I T O C Ho N D R I a U N D E R H Y P O X I Amentioning
confidence: 99%
“…Table 1 shows that Hb transcripts coexist in rice growing under cold, drought and salt stress conditions. Also, Ohwaki and co-workers 83 reported that nshb1 and nshb2 are induced by nitrate, nitrite and NO in cultured rice cells. These observations indicate that rice hb genes response to a variety of stress conditions.…”
Section: Molecular Biology Of Rice Hemoglobinsmentioning
confidence: 97%
“…It has been reported that nsHb1 genes are induced by osmotic stress and high salinity (Taylor et al, 1994;Trevaskis et al, 1997;Lira-Ruan et al, 2001;Zhao et al, 2008;Almada et al, 2013), by treatments with nitrate, nitrite, nitric oxide, salicylic acid, methyl jasmonic acid, and H 2 O 2 (Wang et al, 2000;Sakamoto et al, 2004;Ohwaki et al, 2005;Qu et al, 2006;Sasakura et al, 2006), as well as by deficiencies in minerals such as P, K, and Fe (Wang et al, 2003). ZmHb mRNA levels in maize seedlings are induced by high-salt and osmotic stresses in addition to hypoxic stress (Zhao et al, 2008).…”
Section: Regulation By Osmotic Stress and Mineralsmentioning
confidence: 99%
“…Hemoglobin is also induced by nitrate ions in aleurone layers and in Arabidopsis roots (Nie and Hill, 1997;Wang et al, 2000). Two nsHb1 genes, ORYsa GLB1a and ORYsa GLB1b, were strongly induced by nitrate, nitrite, and nitric oxide (Ohwaki et al, 2005). The induction of the Hb gene by hypoxia is linked to a decrease in ATP levels and is mediated by Ca 2+ (Hebelstrup et al, 2007).…”
Section: Regulation By Osmotic Stress and Mineralsmentioning
confidence: 99%